The Effectiveness of Agility Training on the Improvement of Football Dribbling Skills at SSB Kalegowa - Andi Rizal; Retno Farhana Nurulita (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to determine the effectiveness of agility training on improving dribbling skills in soccer players at SSB Kalegowa. The research employed a quasi-experimental design using a one-group pretest–posttest model with 25 players aged 13–15 years as subjects. The agility training program was implemented for six weeks with a frequency of three sessions per week. Data were collected through the Illinois Agility Test and zig-zag dribbling test and analyzed using the Paired Sample t-test at a significance level of α = 0.05. The results showed that the average pretest time was 12.96 seconds, while the posttest average decreased to 10.87 seconds, with a mean difference of 2.09 seconds. The t-test analysis revealed a value of t = 88.38 with p = 0.000 (p < 0.05), indicating a significant difference between pretest and posttest results. It can be concluded that agility training has a significant effect on improving dribbling performance in soccer players. Agility-based drills effectively enhance coordination, speed, and balance, contributing to better control and efficiency during dribbling.